Poor economics : a radical rethinking of the way to fight global poverty - Banerjee, Abhijit V.; Duflo, Esther, 1972- (New York : PublicAffairs, 2011)
"Billions of government dollars, and thousands of charitable organizations and NGOs, are dedicated to helping the world's poor. But much of the work they do is based on assumptions that are untested generalizations at best, flat out harmful misperceptions at worst. Banerjee and Duflo have pioneered the use of randomized control trials in development economics. Work based on these principles, supervised by the Poverty Action Lab at MIT, is being carried out in dozens of countries. Their work transforms certain presumptions: that microfinance is a cure-all, that schooling equals learning, that poverty at the level of 99 cents a day is just a more extreme version of the experience any of us have when our income falls uncomfortably low. Throughout, the authors emphasize that life for the poor is simply not like life for everyone else: it is a much more perilous adventure, denied many of the cushions and advantages that are routinely provided to the more affluent"--
UNEDITED/Tomas/2011/Jun
Includes bibliographical references and index.
4
Keywords: Economic assistance -- Developing countries; Poverty -- Prevention